The Effect of Leadership and Training on Employee Performance through Competency at PT Pertamina Drilling Services Project Sumatera Bagian Selatanroject Sumatera Bagian Selatan - Ulpa, Aktrilianjas; Asiati, Diah Isnaini; Nurrahmi, Maftuhah (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to determine the effect of leadership and training on employee performance through competency in PT. Pertamina Drilling Services Project South Sumatra. The research type is associated with the variables used: leadership, training, competency, and performance, which are developed into 13 indicators. The population is all employees of PT. Pertamina Drilling Services Project South Sumatra had a total of 532 respondents, of which 130 were taken using probability sampling with a cluster sampling system. The data used is primary data with a questionnaire data collection method and secondary data taken through literature. The analysis technique used by researchers is structural equation modeling (SEM). The results of the study prove that 1) Leadership has a positive and significant effect on competency; 2) Training has a positive and significant effect on competency; 3) Leadership has a positive and insignificant effect on performance; 4) Training has a positive and significant effect on performance; 5) Competency has a positive and significant effect on performance; 6) Leadership has a positive and significant effect on performance through work competency; 7) Training has a positive and significant effect on performance through work competency. Based on the discussion results, it was also proven that competency successfully strengthened the influence of leadership and training on performance.